Hyperacute Therapies for Childhood Stroke: A Case Report and Review of the Literature. (18th July 2010) - Irazuzta, Jose; Sullivan, Kevin J.
Abstract : Objective . The optimal management of pediatric patients with arterial ischemic stroke (AIS) is not known. Despite this, goal-oriented, time-sensitive therapies geared to rapid reestablishment of arterial blood flow are occasionally applied with beneficial effects. The inconsistent approach to AIS is in part due to a lack of knowledge and preparedness. Methods . Case report of a 12-year-old male with right middle cerebral artery (MCA) occlusion resulting in dense left hemiplegia and mutism and review of the literature. Intervention(s) . Mechanical thrombectomy, intra-arterial administration of rt-PA, vasodilators, and platelet inhibitors, and systemic anticoagulation and subsequent critical care support. Results . Restoration of right MCA blood flow and complete resolution of neurologic deficits. Conclusion . We report the gratifying outcome of treatment of a case of AIS in a pediatric patient treated with hyperacute therapies geared to arterial recanalization and subsequent neurologic critical care and review the pertinent literature. Guidelines for the emergency room management of pediatric AIS from prospective, randomized trials are needed.